Health and Safety Executive Work Related Stress Scale - Indonesian Version: Reliability and Convergent Validity - Novika Grasiaswaty; Linda Pradita; Nuri Sadida (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Existing measures of occupational stress often do not count an essential factor that determines the level of worker stress, which is psychosocial factors. The purpose of this study was to examine the psychometric features of an adaptation of the Health and Safety Executive-Work Related Stress Scale (HSE-WRSS), a measure that includes psychosocial factors to measure work stress. Methods: Cronbach alpha was used to determine reliability and convergent validity, by correlating it with other instruments, namely the Employee Well Being (EWB) scale and the neuroticism scale as part of the Big Five Inventory (BFI). Questionnaires were distributed online via Google Forms, and data processing was performed using JASP 12. Results: Data on a total of 210 out of 239 employees were processed for reliability testing and item analysis. Meanwhile, data for 37 employees were processed to be tested for a convergent validity test. The dependability of each dimension was between 0.67-0.82. Meanwhile, item analysis revealed that 33 items had a good Crit value with a correlation between item-total >0.30, whereas 2 items had a bad Crit value with a correlation between item-total 0.30. Correlation analysis revealed a positive and substantial relationship between the HSE-WRSS and the EWB scale, and a negative and significant relationship between the HSE-WRSS and neuroticism. Conclusion: In general, the results of this investigation demonstrate that the HSE-WRSS measurement is trustworthy and valid in the Indonesian version.